2013
DOI: 10.15835/nbha4129179
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Plant Community Changes along a Goat Grazing Intensity Gradient in an Open Canopy Oak Forest

Abstract: Understanding how the management practices of silvopastoral systems affect the long-term sustainability of oak ecosystems and what their influence is on nutrient cycling and plant community, is of great interest. The aim of this study was to examine the effects of relative grazing intensity on soil properties and on vegetation characteristics in an open canopy oak forest dominated by Quercus frainetto. The research was conducted in the area of Pentalofos, which is located in Evros region, north-eastern Greece … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Grazing has also been reported to promote biodiversity (Mountford and Peterken, 2003;Mosquera-Losada et al, 2009). Lempesi et al (2013) results in a grazed oak woodland in northern Greece confirmed the moderate grazing hypothesis (Noy Meyer, 1995;Tilman, 1997) that light and moderate grazing results in an increase of biodiversity. Thus, managed woodland grazing systems are increasingly recognised as being beneficial to woodland biodiversity (McEvoy et al, 2005).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Grazing has also been reported to promote biodiversity (Mountford and Peterken, 2003;Mosquera-Losada et al, 2009). Lempesi et al (2013) results in a grazed oak woodland in northern Greece confirmed the moderate grazing hypothesis (Noy Meyer, 1995;Tilman, 1997) that light and moderate grazing results in an increase of biodiversity. Thus, managed woodland grazing systems are increasingly recognised as being beneficial to woodland biodiversity (McEvoy et al, 2005).…”
Section: Resultssupporting
confidence: 59%
“…These differentiated results can be attributed to the different type of ecosystem and to different type of grazer. Lempesi et al (2013) found that goats browsing affected species diversity of the woody vegetation layer but had minimum impact on the herbaceous vegetation layer.…”
Section: Methodsmentioning
confidence: 95%
“…Therefore, assessments of the consequences of land use management on grassland ecosystems should take the microbial community into consideration. Meanwhile, grazing followed by recovery offers a tool for conservation management, which could improve grassland maintenance if carefully and appropriately executed (Cao et al 2004;Lempesi et al 2013;Pappas and Koukoura 2013). The strong coupling of the microbial community, plants, and soil biogeochemical cycles makes it possible to achieve the best ecosystem service by regulating individual components of the grassland ecosystem.…”
Section: Resultsmentioning
confidence: 99%
“…Higher N levels in soil under grazing have also been reported by Lempesi et al (2013) for an oak forest and by Liu et al (2011) for a grassland, and it is probably caused by animal excrement and urine ( Tamartash et al, 2007). The positive effects of grazing on available P concentrations are probably associated with the dung and urine deposits which are essential sources of a readily mineralizable P source ( Dahlgren et al, 1997).…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that soil OM is also related to grazing intensity ( Chinea et al, 1993). Dahlgren et al (1997) reported no significant effect of light grazing intensity on soil OM in a Quercus douglasii woodland, while Lempesi et al (2013) found that OM gradually decreased as grazing intensity increased in an open canopy of Quercus frainetto forest due to a significant reduction in litter caused by vegetation removal during the grazing process. Reeder et al (2004) reported that the differences in species composition due to grazing might affect the rooting biomass contribution to soil OM and C inputs ( Stewart and Frank , 2008).…”
Section: Discussionmentioning
confidence: 99%